Daily Dynamo Electric Fields Derived by Using Equatorial Ionization Anomaly Crests of the Total Electron Content - Ching‐Chung Cheng; Jann‐Yenq Liu; Charles C. H. Lin; Yin‐Chen Cheng (Space Weather)
Abstract Latitudinal distances between the two equatorial ionization anomaly (EIA) crests in total electron content (TEC) of global ionosphere map (GIM) are used to derive the daily dynamo eastward electric field by comparing the eastward electric field calculated by ROCSAT‐1 vertical ion velocity in four seasons. The electric fields derived by the EIA crests of GIM TEC, ROCSAT‐1 ion velocity, and the incoherent scatter radar (ISR) observations at Jicamarca are generally in good agreement in longitudes and seasons. Meanwhile, the electric fields derived by the EIA crests agree well with those by ROCSAT‐1, FORMOSAT‐7/COSMIC‐2, and Jicamarca ISR on individual days. A long‐term study of the GIM‐TEC crest distance reveals obvious solar activity dependency of the daily dynamo electric field during 1999–2020. These agreements confirm that the EIA crest can be used to derive the daily eastward dynamo electric field and the associated vertical ion velocity which is responsible to the strength of equatorial plasma fountain and the latitudinal extend of the EIA. Moreover, the vertical ion velocity derived by the GIM‐TEC crest distance is further used to improve the SAMI2 model for space weather applications.